2012
DOI: 10.1073/pnas.1204789109
|View full text |Cite
|
Sign up to set email alerts
|

Functional imaging reveals rapid reorganization of cortical activity after parietal inactivation in monkeys

Abstract: Impairments of spatial awareness and decision making occur frequently as a consequence of parietal lesions. Here we used event-related functional MRI (fMRI) in monkeys to investigate rapid reorganization of spatial networks during reversible pharmacological inactivation of the lateral intraparietal area (LIP), which plays a role in the selection of eye movement targets. We measured fMRI activity in control and inactivation sessions while monkeys performed memory saccades to either instructed or autonomously ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
79
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 63 publications
(79 reference statements)
11
79
3
Order By: Relevance
“…Similar findings were also reported for saccade movements after LIP inactivation. Although these results are consistent with previous inactivation studies that used the asynchronous doubletarget paradigm (Wardak et al, 2002;Balan and Gottlieb, 2009), they differ from our findings as well as from those of previous studies (Wilke et al, , 2013 that only used the free-choice and single-target instructed tasks-i.e., reduction of contralesional choices only when both targets are simultaneously presented. These findings and the direct comparison of inactivation effects on single-target trials within and outside of the SOA task (Wardak et al, 2002) demonstrate that the behavioral context (i.e., trying to correctly report the first target, as opposed to free choice between targets associated with equal and deterministic reward in our experiments) strongly affects the pattern of inactivation-induced deficits.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Similar findings were also reported for saccade movements after LIP inactivation. Although these results are consistent with previous inactivation studies that used the asynchronous doubletarget paradigm (Wardak et al, 2002;Balan and Gottlieb, 2009), they differ from our findings as well as from those of previous studies (Wilke et al, , 2013 that only used the free-choice and single-target instructed tasks-i.e., reduction of contralesional choices only when both targets are simultaneously presented. These findings and the direct comparison of inactivation effects on single-target trials within and outside of the SOA task (Wardak et al, 2002) demonstrate that the behavioral context (i.e., trying to correctly report the first target, as opposed to free choice between targets associated with equal and deterministic reward in our experiments) strongly affects the pattern of inactivation-induced deficits.…”
Section: Discussioncontrasting
confidence: 55%
“…However, in the inactivation sessions, the muscimol injection decreases the relative desirability of the contralesional reach options (i.e., drug injection inhibits the PRR neuronal population that encodes the desirability of the contralesional reaches), resulting in a profound choice bias toward ipsilesional targets. The motivational underpinning of inactivation-induced spatial bias is supported by our recent inactivation study of the pulvinar (which is strongly interconnected with PRR), showing that the contralesional choice deficit can be alleviated by placing a large reward in the contralesional hemifield (Wilke et al, 2013). However, the action-based theory and the notion of relative desirability in the PRR provide just a theoretical interpretation of the results and further experimental work is required to validate the hypothesis.…”
Section: Action-based Decision Theory Might Explain the Bias In Reachmentioning
confidence: 81%
See 1 more Smart Citation
“…The dorsal pulvinar is reciprocally interconnected with several areas in the parietofrontal cortex such as the lateral intraparietal (LIP) area, FEF, and the dorsolateral pFC (dlPFC), where electrophysiological studies in monkeys have reported firing rate changes during cue and delay-period intervals in the context of memory saccade tasks (Takeda & Funahashi, 2002;Chafee & Goldman-Rakic, 1998;Gnadt & Andersen, 1988). Correspondingly, several studies demonstrated that lesions in these areas impair performance in memory saccade tasks (Wilke, Kagan, & Andersen, 2012;Liu, Yttri, & Snyder, 2010;Dias & Segraves, 1999;Li, Mazzoni, & Andersen, 1999;Funahashi, Bruce, & Goldman-Rakic, 1993). These studies revealed that LIP and FEF inactivation were associated with longer latencies and hypometric saccades toward contralesional positions (Dias & Segraves, 1999;Li et al, 1999), whereas dlPFC lesions did not result in longer latencies but were characterized by erroneous saccade directions (Funahashi et al, 1993).…”
Section: Pulvinar and Oculomotor Behaviormentioning
confidence: 90%
“…Since previous studies investigating face patches often relied on anatomically defined atlases, we have also constructed a probabilistic retinotopic atlas of monkey ventral extrastriate cortex that can be used to compare past, and to guide future, fMRI, electrophysiology (Issa and DiCarlo, 2012;Popivanov et al, 2012), and focal-perturbation experiments (Ekstrom et al, 2008;Gerits et al, 2012;Wilke et al, 2010Wilke et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%